Referrals among VCs and the length of due diligence: The effect of relational embeddedness - Guenther, Christina; Özcan, Serden; Sassmannshausen, Dirk (Journal of Business Venturing, 2022)
Venture capital is a socially embedded business where VCs refer investment opportunities to one another. While we know that these referrals increase the chances of a start-up passing the initial screening process, we investigate to what extent the intensity of relational embeddedness between referrer and referee relates to the length of the due diligence process of the start-up being referred. Extending information processing theory by social network theory arguments, we argue that referees have access to more and better information during the due diligence as relational embeddedness increases. This will lead to a more in-depth and rigorous evaluation. Moreover, the referee will be subject to social obligations to invest additional resources in the assessment, the more so, the stronger the relational embeddedness. Both factors lead to a prolongation of the due diligence process. Furthermore, we find that the individual investment manager's current performance and experience moderate this relationship.